Produção de biossurfactante por Bacilllus licheniformis utilizando rejeito do abacaxi (Ananas comosus L.) como fonte renovável e de baixo custo - Almeida, Fabiola Carolina Gomes de (2010)
The biosurfactants are substances that can have characteristics surfactants, being called biosurfactants, which can be produced by bacteria and fungi when grown on different carbon sources as a result of their metabolism. In the present study explores the potential of biotechnology of Bacillus licheniformis UCP 1016, soil bacteria isolated from the Port of Recife contaminated by oil, biosurfactant production using the house of pineapple (Ananas comosus L.) as an alternative. Initial trials were conducted to evaluate the production of bioemulsificante by the detection of hemolytic activity and degradation of diesel and kerosene. From these results, studies were conducted with the production of pineapple in the middle bioemulsificante control and different concentrations of hydrophobic substrates (diesel and kerosene to 5 and 10%) as supplements. The vials were incubated at 35 ° C, 150rpm for 72 hours, evaluating the kinetics of growth, emulsification index and surface tension. With the best condition for obtaining the bioemulsificante was used cell-free metabolic net was used for the removal of oil and motor oil, as well as stability tests and phytotoxicity. Initial results with B. licheniformis showed hemolytic activity and ability to grow new medium formulated with pineapple peel (9.5 x 106 CFU / mL), as well as supplements diesel (9.8 x 106 CFU / mL) and kerosene (8.0 x105 CFU / mL), 72 h of culture. The lowest surface tension was reduced by 57.73 ± 0.15 mN / m to 38.32 ± 0.16 mN / m, in the middle of production with 5% diesel. Stability tests showed that bioemulsificante was stable at pH 2 and 4 in 8% NaCl and no toxicity. The cell-free metabolic net was able to remove 95.15% and 85.55% of oil burned motor oil, respectively. Results suggest the formulation of a medium and low-cost alternative for producing bioemulsificante. The bacterium B. licheniformis was found to be a promising microorganism, with potential for application in bioremediation processes